Теоретико-методические аспекты использования инновационных технологий в спортивной подготовке дзюдоистов - Ковш, Н.А.; Плетнёв, А.С. (My University, 2013)
Subject, aims, objects, requirements and specific ways of practicing innovative technolo- gies in judoists’ education and sport training are revealed in this article. The author represents adoption results of sport training original program for sport groups of 1st and 2nd year students using innovative technologies which was held in Kostanai Regional Children’s and Youth Sport School of Olympic Reserve.